2020
DOI: 10.1038/s41598-020-76668-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioelectrochemical treatment of petroleum refinery wastewater with Labaneh whey as co-substrate

Abstract: Petroleum refinery wastewater (PRW) that contains recalcitrant components as the major portion of constituents is difficult to treat by conventional biological processes. Microbial fuel cells (MFCs) which also produce renewable energy were found to be promising for the treatment of PRW. However, due to the high total dissolved solids and low organic matter content, the efficiency of the process is limited. Labaneh whey (LW) wastewater, having higher biodegradability and high organic matter was evaluated as co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Nevertheless, COD removal was further enhanced with the SRB-enriched Fe 3 O 4 @CF electrode where 75 ± 2.1% COD removal was accomplished ( Figure 3A ). The accelerated biodegradation of tannery wastewater in the MFCs with SRB enriched-Fe 3 O 4 @CF can be attributed to the anode electrode which provides a pathway for electron transfer to the cathode via an external circuit that can eventually boost the metabolic rate of microbes in the presence of these non-exhaustible electron acceptors ( Mohanakrishna et al, 2020 ; Hu et al, 2018 ). Furthermore, the improvement in tannery wastewater biodegradation rates attributed to SRB cultures suggests the enrichment of microbes which were highly specific to the biodegradation of recalcitrant pollutants in tannery wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, COD removal was further enhanced with the SRB-enriched Fe 3 O 4 @CF electrode where 75 ± 2.1% COD removal was accomplished ( Figure 3A ). The accelerated biodegradation of tannery wastewater in the MFCs with SRB enriched-Fe 3 O 4 @CF can be attributed to the anode electrode which provides a pathway for electron transfer to the cathode via an external circuit that can eventually boost the metabolic rate of microbes in the presence of these non-exhaustible electron acceptors ( Mohanakrishna et al, 2020 ; Hu et al, 2018 ). Furthermore, the improvement in tannery wastewater biodegradation rates attributed to SRB cultures suggests the enrichment of microbes which were highly specific to the biodegradation of recalcitrant pollutants in tannery wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…A 75 μm mesh sieve was used to sieve the crushed kaolin. To make a slurry, a known quantity (400 g) of crushed kaolin was soaked in 1000 cm 3 of distilled water for a week. The supernatant was decanted until the distilled water became colorless and the slurry was dried (overnight) at 100 °C.…”
Section: Kaolin Pretreatmentmentioning
confidence: 99%
“…1 The direct discharge of untreated petroleum wastewater has contaminated surface and groundwater resources with petrochemical products and consequently poses a significant risk to human health as well as animal life. 2,3 It has been reported that ca 3500-5000 L of petroleum wastewater are generated per tonne of crude oil processed. The wastewater generated from petrochemical industries contains several heavy metals such as vanadium, copper, cadmium, selenium, chromium, iron, lead and nickel, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum efficiency (89%) detected at the applied voltage of 500 mV was nearly 50% higher than that of the control system (59%), which implied the effectiveness of auxiliary voltage in the treatment of PRW. Mohanakrishna et al (2020) added labneh whey as a co-substrate to improve the bio-electrochemical treatment of PRW in a dual-chamber MFC. The results showed a moderate removal efficiency (63.1%) for COD.…”
Section: Introductionmentioning
confidence: 99%